Multiple recurrences from cervical cancer presenting as skin metastasis of different morphologies - Vatsala Katiyar; Tiago Araujo; Nasma Majeed; Nicholas Ree; Shweta Gupta (Elsevier, 2019)
Skin metastasis is an infrequent manifestation in oncology, with reported incidence of about 1.3% in cervical cancer. When present, it usually signals advanced disease with very limited, mostly palliative treatment options. Here we present a patient who was diagnosed with cervical cancer at an early stage and later recurred twice with skin lesions of different morphologies.